(untitled) (Italian Journal of Public Health, 2009)
Background: The utilization of single-use percutaneous catheters (SUDs) is a common practice in interventional cardiology, but the increasing of cardiac interventions and the consequent economic load demand for assessing SUDs’ reuse. The study aimed at estimating the potential saving for Italian cardiology departments in the hypothesis that reprocessing and reuse of SUD is performed by guaranteeing safety and efficiency of the reconditioned device as high as the new marketed one. Methods: A cost-minimization model was applied from the perspective of the health national service. Input parameters for the model were settled by reviewing published data on technical, hygiene and functional properties of reprocessed electrophysiology (EP) and percutaneous transluminal coronary angioplasty (PTCA) catheters. Potential saving at department level was calculated as percentage of the actual expenditure for purchasing single-use devices. Two-ways sensitivity analysis was conducted on main cost drivers. Finally, saving at national level was estimated. Results: The revision of technical and safety data showed the feasibility of reprocessing and reuse of EP and PTCA catheters under determined constrains. Potential savings of 39%, and 12% were calculated at department level for EP and PTCA catheters, respectively. Sensitivity analysis showed saving was dependent primarily on departmental workload. Major variations in saving occurred in the range between one and 200 catheters per year. The cut-off between benefit and charges was also related to regeneration rate and maximum number of uses. The estimate of potential saving at national level ranged in the interval from €19.85M to €24.24M. Conclusions:When safety and efficiency is assured by certified reuse processing, substantial saving could be achieved both at departmental and national level contributing to optimize budget allocation for the healthcare system.